#### Answer

f and g are inverses of each other

#### Work Step by Step

g(f(x)) = g(3x + 4) =$ \frac{3x + 4 - 4}{3}$ = x
f(g(x)) = f($\frac{x - 4}{3}$) = 3($\frac{x - 4}{3}$) + 4 = x - 4 + 4 = x
Since g(f(x)) = f(g(x))

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

f and g are inverses of each other

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.